INEFFECTIVE BREATHING PATTERN NURSING CARE WITH CHRONIC KIDNEY DISEASES PATIENT - ilkafah, Ilkafah; Fujiyah, Eka Fatmah; Purwanto, Cucuk Rahmadi; Susanto, Joko; Lutfiandini, Cherlys Tin (Journal of Vocational Nursing, 2022)
Introduction: Patient with Chronic Kidney Disease (CKD) will get a failure to breathing because of fluid accumulation in the lung. Patients with CKD will not be able to breathe normally, so the main problem that often occurs is an ineffective breathing pattern.  This study aims to explore nursing care for patients with ineffective-breathing pattern in patient with CKD at Soegiri Lamongan hospital. Methods: The design of this research is qualitative with a case study, the methods of data collection through interviews, observations, physical examinations and documentation studies. The data obtained were analyzed by comparing case reviews and literature reviews. Results: The results of the problems for nursing diagnosis that arise are CKD with ineefective-breathing pattern. Interventions that are emphasized and carried out in the field in the case study are providing a semi-fowler/ fowler position, and maintaining oxygen therapy. Final evaluation of nursing diagnoses in patients with problems resolved and goals achieved according to the specified time criteria. Conclusions: The study indicated that ineefective breathing pattern can be solved by positioning a semi-fowler or half-sitting position, decrease fluid intake and correcting anemia. Suggestions for nurses to focus in developing science and technology to be applied to all nursing personnel in providing nursing care for ineffective breathing patterns for patients with chronic kidney disease.